A microelectrode array electrodeposited with reduced graphene oxide and Pt nanoparticles for norepinephrine and electrophysiological recordings. (22nd September 2017) - Wang, Li; Song, Yilin; Zhang, Yu; Xu, Shengwei; Xu, Huiren; Wang, Mixia; Wang, Yang; Cai, Xinxia
Abstract: Norepinephrine (NE), a common neurotransmitter released by locus coeruleus neurons, plays an essential role in the communication mechanism of the mammalian nervous system. In this work, a microelectrode array (MEA) was fabricated by micro-electromechanical system (MEMS) technology to provide a rapid, sensitive and reliable method for the direct determination in NE dynamic secretion. To improve the electrical performance, the MEA was electrodeposited with the reduced graphene oxide and Pt nanoparticles (rGOPNps). rGOPNps-MEA was investigated using scanning electron microscopy, atomic force microscopy and electrochemical impedance spectroscopy, differential pulse voltammetry exhibited remarkably electrocatalytic properties towards NE. Calibration results showed a sensitivity of 1.03 nA µ M −1 to NE with a detection limit of 0.08 µ M. In Particular, the MEA was successfully used for measuring dynamic extracellular NE secretion from the locus coeruleus brain slice, as well as monitoring spike firing from the hippocampal brain slice. This fabricated device has potential in studies of spatially resolved delivery of trace neurochemicals and electrophysiological activities of a variety of biological tissues in vitro .